PENGEMBANGAN BAHAN AJAR PEMBELAJARAN PJOK MATERI LEMPAR BERBASIS MULTIMEDIA INTERAKTIF ARTICULATE STORYLINE PADA SISWA KELAS VII - Firdaus, Muhammad Anwar; Nurrochmah, Siti; Supriyadi, Supriyadi (Fakultas Ilmu Keolahragaan Universitas Negeri Malang, 2024)
The purpose of writing this development research is to develop PJOK teaching materials, interactive multimedia-based throwing material, articulate storyline for class VII students at MTs Negeri Tulungagung, presenting clarity, interest, convenience and usefulness of content as a medium for learning throwing movements which previously was done only when children wanted to move with limited study hours. limited. The